2023
DOI: 10.1155/2023/9504296
|View full text |Cite
|
Sign up to set email alerts
|

Antihelminthic Activity of Lophira Lanceolata on Heligmosomoides polygyrus Using an Automated High-Throughput Method

Abstract: Background. There are about 13 parasitic infections that are responsible for significant morbidity and mortality but have not received the attention they deserve; thus, they are now known as “neglected tropical diseases” (NTDs). This study was aimed at evaluating the antihelminthic activities of Lophira lanceolata using an automated high-throughput method. Methods. The antihelminthic activity effect of the extracts against H. polygyrus was determined using an automated high-throughput method. For the egg-hatch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…The larvicidal activity was determined using the worm microtracker method described by Cédric et al [ 13 ]. The L1 and L2 larvae were put in contact with extracts with the same concentrations as the ovicidal activity (5–0.3125 mg/mL) and incubated for 24 hours in a final volume of 200 μ L. The percentage of inhibition of larvae motility was determined [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The larvicidal activity was determined using the worm microtracker method described by Cédric et al [ 13 ]. The L1 and L2 larvae were put in contact with extracts with the same concentrations as the ovicidal activity (5–0.3125 mg/mL) and incubated for 24 hours in a final volume of 200 μ L. The percentage of inhibition of larvae motility was determined [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…Eggs. The collection of eggs was done using the flotation technique described by Cédric et al [13]. After the collection of fresh eggs, it was incubated at 25 °C for 24 hours for the obtention of embryonated eggs and used for the evaluation of hatching.…”
Section: Production Of Embryonatedmentioning
confidence: 99%
See 1 more Smart Citation
“…Barks. The ethanol extract was obtained using the method described by Cedric et al [10]. Briefly, 100 g of L. lanceolata powder was introduced into 1 l of 95% ethanol and remained in the solvent for 72 hours with occasional stirring.…”
Section: Preparation Of the Ethanol Extract Of L Lanceolata Stemmentioning
confidence: 99%
“…The ethanol extract showed interesting plasmodial activity, revealing an IC 50 of 31.865 and 24.515 μ g/ml for the sensitive and resistant strains, respectively, and a resistance index of 0.01 (IR = 0.01). et al [ 10 ] recently demonstrated the antihelminthic activity of L. lanceolata . Similarly, according to Sinan et al [ 11 ], the chemical profiling of L. lanceolata confirmed the presence of lanceolatins and lophirones.…”
Section: Introductionmentioning
confidence: 99%